Role of Assessment for Learning of Science at School Level - Garg, Rachna (SCHOOL SCIENCE, 2014)
For being able to do effective assessment, it is desirable that science educators have adequate knowledge of the role that assessment plays in science education. This article discusses how the role of assessment has changed over a period of time and how these changes have impacted the assessment practices. It describes how the assessment practices have been influenced by developments in psychology and philosophy in the last one century. The benefits of using Assessment for Learning (AfL) of science and the various challenges which need to be overcome to reap these benefits are also explained.